Zika virus viewed through the resonant recognition model. Unraveling new avenues for understanding and managing a serious threat - Cáceres, José Luis Hernández; Wright, Graham (European Journal for Biomedical Informatics, 2018)
Introduction: Zika Virus (ZIKV) infection is a major public health concern, affecting almost each country in the western hemisphere. A more than 20-fold increase in microcephaly risks is associated to ZIKV infection in pregnancy. A new vaccine is not expected before 2019, and alternative prophylactic and therapeutic approaches are encouraged. We expect that the Resonant Recognition Model, developed by Irena Cosic, might lay on the basis for an alternative approach to handle ZIKV. Objective: We tried to identify the resonant frequencies associated to the ZIKV polyprotein and their use for an automatic taxonomy of different ZIKV strains. We put to test the hypothesis of interaction between ZIKV envelope protein and the AXL receptor, one of the plausible mechanisms proposed for ZIKV associated microcephaly. Results: Four relevant frequencies (fRRM) were found in ZIKV polyprotein consensus spectrum. Corresponding four spectral amplitudes allowed separating African from Asian/American ZIKV isolates (k-means clustering). Peak 3 (fRRM= 0.2754) and Peak 4 (fRRM= 0.334) yielded a finer separation between Asian sequences and those from the current outbreak collected in 2015 (Asian/American). Consensus spectrum for pooled Dengue virus and ZIKV polyprotein sequences suggest that Peak 4 might be a specific hallmark of ZIKV. RRM results support the interaction between ZIKV envelope protein and AXL membrane receptor. The interacting frequency of fRRM= 0.167 seems to be a sub-harmonic of Peak 4. Conclusions: Resonant recognition model provides a plausible view of processes involved in the interactions of ZIKV with the human host, and is suggesting the exchange of electromagnetic radiation at the frequencies of 601.8nm (yellow light) and 1203.6 (near infrared) during ZIKV envelope protein with the AXL receptor in the human fetal tissue. This information might be relevant for alternative approaches to new therapeutic approaches to treat ZIKV-associated damage to newborns.
Keywords: Polyproteins; virus zika; polyproteiny; Gene Products, env; genové produkty env; Flavivirus; Zika Virus Infection; Electromagnetic Phenomena; electron-ion interaction potential; elektromagnetické jevy; Zika Virus; infekce virem zika